ASUHAN KESEHATAN GIGI DAN MULUT PADA KLIEN TN. DF DENGAN KELUHAN KARANG GIGI - Nur Fauziah Yulyanti; Deru Marah Laut; Dewi Sodja Laela; Yonan Heriyanto (Poltekkes Kemenkes Bandung, 2022)
The bad habit of smoking makes tar, one of the components in cigarettes, which is sticky, making it easier for plaque to stick to the surface of the teeth. Plaque that is not cleaned properly over time will form tartar. Tartar can cause discomfort to a person, as well as client Mr. DF who felt disturbed and uncomfortable with this tartar. This study aims to determine the results of Dental and Oral Health Care on the client of Mr. DF (26 Years) with complaints of tartar at the clinic of the Department of Dental Health Bandung. This research method is a case report with the concept of dental and oral health care which consists of a process of assessment, diagnosis, planning, implementation and evaluation. This report describes cases of tartar and bad smoking habits. The results of the initial assessment found tartar with a score of 19, stain, 4 teeth with caries, 1 remaining root of the tooth and free plaque score of 35%. After the examination, it was stated that the results of the diagnosis were that there were 5 human needs that were not met. To fulfill these 5 basic human needs, scaling, stain cleaning, fillings, tooth extraction, counseling using the Chair Side Talk and Oral Physiotherapy. The evaluation results show that the 8 basic human needs of the client have been met after treatment.